The Clinical Significance of Hepatic CD69+CD103+CD8+ Resident‐Memory T Cells in Autoimmune Hepatitis. Issue 2 (22nd June 2021) - You, Zhengrui; Li, You; Wang, Qixia; Zhao, Zhibin; Li, Yikang; Qian, Qiwei; Li, Bo; Zhang, Jun; Huang, Bingyuan; Liang, Jubo; Chen, Ruiling; Lyu, Zhuwan; et al.
Abstract : Background and Aims: The diverse inflammatory response found in the liver of patients with autoimmune hepatitis (AIH) is well established, but identification of potentially pathogenic subpopulations has proven enigmatic. Approach and Results: We report herein that CD69 + CD103 + CD8 + tissue‐resident memory T cells (TRM ) are significantly increased in the liver of patients with AIH compared to chronic hepatitis B, NAFLD, and healthy control tissues. In addition, there was a significant statistical correlation between elevation of CD8 + TRM cells and AIH disease severity. Indeed, in patients with successful responses to immunosuppression, the frequencies of such hepatic CD8 + TRM cells decreased significantly. CD69 + CD8 + and CD69 + CD103 + CD8 + T cells, also known as CD8 + TRM cells, reflect tissue residency and are well known to provide intense immune antigenic responses. Hence, it was particularly interesting that patients with AIH also manifest an elevated expression of IL‐15 and TGF‐β on inflammatory cells, and extensive hepatic expression of E‐cadherin; these factors likely contribute to the development and localization of CD8 + TRM cells. Based on these data and, in particular, the relationships between disease severity and CD8 + TRM cells, we studied the mechanisms involved with glucocorticoid (GC) modulation of CD8 + TRM cell expansion. Our data reflect that GCs in vitro inhibit the expansion of CD8 + TRM cells induced by IL‐15 and TGF‐β and with direct down‐regulation of the nuclear factor Blimp1 of CD8 + TRM cells. Conclusions: Our data suggest that CD8 + TRM cells play a critical role in the pathogenesis of AIH, and GCs attenuate hepatic inflammation through direct inhibition of CD8 + TRM cell expansion.